Efficiency or Trust? Reforming Waqf in Indonesia Through a Tale of Two Waqf Models (Singapore and South Africa) - Lusiana Handayani; Tika Widiastuti; Raditya Sukmana; Magda Ismail A. Mohsin (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2025)
Abstract: Effective waqf governance is essential for unlocking the full socioeconomic potential of waqf institutions. This paper compares two differentgovernance models: the state-led, top-down approach in Singapore and thecommunity-based, bottom-up model in South Africa. By analyzing the strengthsand weaknesses of each, the study aims to draw lessons for Indonesia, a countrydealing with systemic governance issues. The research employs a qualitative,comparative methodology, utilizing thematic analysis facilitated by NVivosoftware to systematically code and synthesize existing findings from the threenations. The analysis reveals that Singapore's centralized model offers significantefficiency and robust oversight. Still, it also introduces regulatory rigidity that canhinder smaller institutions and raise trust issues within the community.Conversely, South Africa’s independent model has successfully created acomprehensive governance system and promoted public trust; however, it faceslogistical challenges in coordinating volunteers and managing leadershipsuccession. The findings on Indonesia point out critical weaknesses, includingpoorly developed and uncoordinated regulations, a widespread lack ofaccountability among waqf managers (nazhir), and low professional skills.Thepaper concludes that no single model is universally superior. The key implicationfor Indonesia is that reform should not focus on wholesale adoption of an externalmodel. Instead, the central recommendation is the implementation of a robustperformance measurement framework. Such a framework can serve as afoundational tool to build a hybrid model, enabling data-driven, top-downregulation while empowering bottom-up institutional improvement, therebyaddressing the nation's unique challenges.Keywords: Waqf Governance, Performance Measurement, Accountability, TopDown Governance, Bottom-Up Governance